PEMBUATAN NATA BERBAHAN DASAR ALANG-ALANG SECARA FERMENTASI SEBAGAI KAJIAN AWAL PEMBUATAN EDIBLE FILM - Agnesia Permatasari; Hafsah Fajrin Aprilianti; Aprilina Purbasari (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
Nata is a kind of food fermented by Acetobacter xylinum bacteria, which is forming a gel which floats on the surface of the media or places that contain sugar. Reed plants contain glucose ± 6.8% so it can be used nata. Nata can be harnessed into goods that have a higher economic value, among which are the edible film. Purpose of this study was to determine the effect of concentration of the added starter (Acetobacter xylinum) and influence the level of acidity (pH) in the process of making nata, furthermore nata can be used for manufacture of  edible film. Major in this prosedur there are two steps, first fermentation nata and the second is the manufacture of edible main film. Variable in this study are the variation of pH of 3, 4 and 5 and starter concentration of 10%, 20% and 30%. Optimal result from this study at pH 4 and concentration 30%. This means the addition of 30% of the activity of bacteria Acetobacter xylinum are on optimal conditions in which the starter to the maximum 30% sufficient for the formation of nata. From the results of experiments conducted, the resulting edible film with a thickness of 0.05 mm, tensile strength of 6.635 N/mm2, edible films can be used as food packaging materials with tensile strength values ​​ranged from 2.89 to 27.26 N/mm2 making edible films nata produced from reeds can be used for food packaging materials.